Pengaruh Prinsip Keadilan dan Prinsip Kejujuran Dalam Etika Bisnis Islam Terhadap Minat Beli Konsumen di Pasar Tradisional Wadungasri - Riyadul Mubtadiah; Mochammad Su'eb (eCo-Fin, 2025)
Business ethics play a crucial role in ensuring the long-term success of an organization, as they provide guidance for ethical and responsible decision-making. In the context of Islam, business ethics, known as Islamic business ethics represent a framework of moral values and rules that regulate business activities in accordance with Islamic teachings. These principles emphasize fairness in transactions, honesty in presenting products, and equality in treating customers. This study examines (1) the effect of fairness as an Islamic business ethics principle on consumer purchase intention, and (2) the influence of honesty on consumer purchase intention. The research uses a quantitative approach with multiple linear regression analysis. Data were obtained through questionnaires and observations, then analyzed using validity tests, classical assumption tests, and hypothesis testing. The results show that the fairness variable has an influence value of 3.127, while the honesty variable has a higher influence value of 5.710. Among the two, honesty (X2) emerges as the most dominant factor affecting consumer purchase intention, with a standardized coefficient value of 0.547, indicating a strong and direct relationship.